Visions of justice Sharia and cultural change in Russian Central Asia - Sartori, Paolo 1975- (Handbook of oriental studies = Handbuch der Orientalistik. Section eight, Uralic and Central Asian studies, 2017)
Visions of Justice offers an exploration of legal consciousness among the Muslim communities of Central Asia from the end of the eighteenth century through the fall of the Russian Empire. Paolo Sartori surveys how colonialism affected the way in which Muslims formulated their convictions about entitlements and became exposed to different notions of morality. Situating his work within a range of debates about colonialism and law, legal pluralism, and subaltern subjectivity, Sartori puts the study of Central Asia on a broad, conceptually sophisticated, comparative footing. Drawing from a wealth of Arabic, Persian, Turkic and Russian sources, this book provides a thoughtful critique of method and considers some of the contrasting ways in which material from Central Asian archives may most usefully be read.